2008
DOI: 10.1007/s11751-008-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of stable and unstable proximal femoral fractures with a new trochanteric nail: results of a multicentre study with the Veronail

Abstract: The incidence of hip fractures continues to rise. This study is the first evaluation of a new intramedullary implant, the Veronail, that provides double axis fixation into the femoral head and allows the surgeon to choose whether to use sliding or fixed locked proximal screw fixation for trochanteric femoral fractures. The fractures were classified according to the AO classification, and function was assessed with the Modified Harris Hip Score. 111 patients with trochanteric fractures were evaluated in eight I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…I evaluated results and compared them with those obtained from various published studies. In my study, proximal femur fractures were more common after 5th decade with a mean age group of 56.4 years where as in the studies of Franco et al (2008) [24] , Shan-Wei Yang et al (2012) [25] and Bhakat et al(2013) [26] who had an mean age of 79.3 years, 53 years and 67.8 years respectively. The sex ratio as per this study was male: female=2.3:1.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…I evaluated results and compared them with those obtained from various published studies. In my study, proximal femur fractures were more common after 5th decade with a mean age group of 56.4 years where as in the studies of Franco et al (2008) [24] , Shan-Wei Yang et al (2012) [25] and Bhakat et al(2013) [26] who had an mean age of 79.3 years, 53 years and 67.8 years respectively. The sex ratio as per this study was male: female=2.3:1.…”
Section: Discussionsupporting
confidence: 56%
“…Out of 60 patients, there were 42 male (70%) patients and 18 female (30%) patients. While in Franco et al (2008) [24] and Bhakat et al (2013) [26] study, more patient were female 81 out of 111 (73%), and 17 out of 30 (60%) respectively. In our study increased incidence in male as compare to female is due to their involvement in riding vehicles, heavy agriculture, labour and more outdoor activities.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…That study contained no control arm, and as a result one is not able to draw conclusions with regard to the optimum treatment of this fracture pattern. In a study evaluating the VeroNail (Orthofix, Verona, Italy) with locked converging screws, patients with unstable proximal femoral fractures had the same function as those managed with a sliding hip screw 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Three cases of cut-out, associated with malposition of the proximal lag screws, occurred with the ENDOVIS nail. In a study of Veronail, another nail, Lavini et al [31] observed screw cut-out in 4.5% of cases. In our study, the lag screw was inserted close to the subchondral bone, and the hip pin superior to the femoral head.…”
Section: Discussionmentioning
confidence: 97%